Matrix Metalloproteinase-7 Is a Urinary Biomarker and Pathogenic Mediator of Kidney Fibrosis - Zhou, Dong; Tian, Yuan; Sun, Ling; Zhou, Lili; Xiao, Liangxiang; Tan, Roderick J.; Tian, Jianwei; Fu, Haiyan; Hou, Fan Fan; Liu, Youhua (Journal of the American Society of Nephrology, 2017)
Matrix metalloproteinase-7 (MMP-7), a secreted zinc– and calcium–dependent endopeptidase, is a transcriptional target of canonical Wnt/ β -catenin signaling. Because Wnt/ β -catenin is activated in diseased kidney, we hypothesized that urinary MMP-7 level may be used as a noninvasive surrogate biomarker for fibrotic lesions. To test this hypothesis, we conducted a cross-sectional study, measuring urinary MMP-7 levels in a cohort of 102 patients with CKD. Compared with normal subjects, patients with various kidney disorders had markedly elevated urinary levels of MMP-7. Furthermore, urinary MMP-7 levels closely correlated with renal fibrosis scores in patients. In mice, knockout of MMP-7 ameliorated the fibrotic lesions and expression of matrix genes induced by obstructive injury. Genetic ablation of MMP-7 also preserved E-cadherin protein expression and substantially reduced the expression of total and dephosphorylated β -catenin and the de novo expression of vimentin and fibroblast-specific protein 1 in renal tubules of obstructed kidneys. In vitro , MMP-7 proteolytically degraded E-cadherin in proximal tubular cells, leading to β -catenin liberation and nuclear translocation and induction of β -catenin target genes by a mechanism independent of Wnt ligands. Finally, pharmacologic inhibition of MMP-7 immediately after obstructive injury reduced renal fibrosis in vivo . These results suggest that MMP-7 not only can serve as a noninvasive biomarker but also is an important pathogenic mediator of kidney fibrosis.